Lifting the Coconut Shell Covering the Malays: Sejarah Melayu, Text Books and Abdullah Munsyi: (Menyingkap Tempurung Orang Melayu: Sejarah Melayu, Buku Teks dan Abdullah Munsyi) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
This paper was written in honour of the Malaysian poet laureate Muhammad Haji Salleh on his 70th birthday. It traces the development of the printed editions of the Sulalatus Salatin published in Southeast Asia and Europe and argues that alterations do not occur in the printed texts. The first published Malay edition was edited by Abdullah bin Abdul Kadir Munsyi in collaboration with the American missionary, Alfred North, in Singapore. The introduction to this first edition was an extract from texts in Sejarah Melayu and concurrently produced as a text book. This article is aimed at discussing the impact of Abdullah's works in the Malay world and the 'fate' of the text books whilst reviewing the editing processes conducted by colonial administrators.Keywords: Sejarah Melayu, Abdullah Munsyi, editing process, colonial administrator